Intensitas Serangan Jamur Ganoderma sp Pada Perkebunan Kelapa Sawit Lahan Mineral dan Lahan Pasang Surut - Rahmana, Billy Aditia; Hayata, Hayata; Hartawan, Rudi (Universitas Batanghari, 2024)
Stem rot disease caused by fungus (Ganoderma sp) is a major challenge in oil palm farming. This fungus infects oil palm trees at every stage of growth. This disease has a gradualy development, which the symptoms only appearing in the last stages, so it is called as